2020
DOI: 10.1097/ico.0000000000002373
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Morphology and Thickness Alterations in Patients With Severe Obstructive Sleep Apnea–Hypopnea Syndrome

Abstract: Purpose: To investigate central endothelial cell density (ECD), morphology, and central corneal thickness (CCT) in patients newly diagnosed with severe obstructive sleep apnea–hypopnea syndrome (OSAHS) and to determine the correlation between these parameters and OSAHS severity. Methods: This prospective, comparative case series was conducted in a university ophthalmology clinic. In total, 51 patients recently diagnosed with severe OSAHS (apnea–hypopnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Corneal endothelial cells are known to be susceptible to oxidative stress, 19 and there are 2 studies 16,17 implying corneal endothelium alterations in patients with OSAHS, probably because of oxidative stress induced by chronic hypoxia. ECD values 16 and %Hex 17 have been found to decrease, whereas CV 17 has been found to increase in patients with untreated OSAHS. There are also a few studies 13,15,16 suggesting that CCT is significantly lower in patients with untreated OSAHS when compared with healthy individuals, possibly because of the hypoxia and hypercapnia induced in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal endothelial cells are known to be susceptible to oxidative stress, 19 and there are 2 studies 16,17 implying corneal endothelium alterations in patients with OSAHS, probably because of oxidative stress induced by chronic hypoxia. ECD values 16 and %Hex 17 have been found to decrease, whereas CV 17 has been found to increase in patients with untreated OSAHS. There are also a few studies 13,15,16 suggesting that CCT is significantly lower in patients with untreated OSAHS when compared with healthy individuals, possibly because of the hypoxia and hypercapnia induced in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature which have analyzed the corneal morphological [13][14][15][16][17] characteristics of patients with OSAHS, indicating that there is an insult to the corneal endothelium and corneal thickness, probably due to oxidative stress induced by chronic hypoxia. So far, no study has elucidated the therapeutic effectiveness of CPAP on the corneal morphometric variables.…”
mentioning
confidence: 99%
“…The relationship between OSA and CCT is controversial with some studies showing diminished CCT with OSA compared with controls [9][10][11] and other studies showing no difference. [12][13][14] Future multivariate analyses or prospective studies could determine whether OSA is a significant contributor to the relationships observed between IOP, CCT, and MetS.…”
Section: Response To Letter To the Editor: Association Of Metabolic S...mentioning
confidence: 99%
“…Since IOP was no longer significant after adjusting for CCT, our data suggested the primary metric associated with MetS in patients with GON was CCT. The relationship between OSA and CCT is controversial with some studies showing diminished CCT with OSA compared with controls9–11 and other studies showing no difference 12–14. Future multivariate analyses or prospective studies could determine whether OSA is a significant contributor to the relationships observed between IOP, CCT, and MetS.…”
mentioning
confidence: 97%
“…See et al conducted a nationwide population-based matched case–control study and found no significant association between KC and SA [ 108 ]. Topographic and biomechanical corneal variations (corneal volume, corneal elevation, and minimum radius) [ 109 ], as well as greater pleomorphism and polymegathism of the corneal endothelium [ 110 ], were found in severe OSA when compared to healthy subjects. The percentage of rapid eye movement sleep, which helped corneal oxygenation and usually decreased in patients with OSA, was also negatively correlated with central corneal thickness [ 110 ].…”
Section: Osa-associated Complications In Anterior Segment Of Eyementioning
confidence: 99%